GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU REMAJA TERHADAP ABORTUS PROVOCATUS DI SMA NEGERI 1 SLIYEG KABUPATEN INDRAMAYU - Tika Fatikhah; Santosa Santosa (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Abortion became one of the serious problems and hadn’t been solved for the woman, the teenagers and the collegeans. Based on the high rate of abortion from year to year, it was increased. Wheres the adolescence was about thirteen up to twenty one years old and at the same time, the physical growth and the sexuality grew up too.Objective : To know the description of the knowledge, the attitude and the behavior of the students at SMA Negeri 1 Sliyeg, Indramayu regency.Method : This research was the descriptive study research which used the cross sectional data accumulation. The sample was 106 respondents, taken from the assessment criteria of the knowledge, the attitude and the behavior toward the provocatus abortion.Result : The research showed that 64 respondents (61,32%) understood well about the provocatus abortion and 81 respondents (76,41%) paid attention to it. While 99 respondents (93,44%) had the low risk sexual behavior of it.Conclusion : The students at SMA Negeri 1 Sliyeg, Indramayu regency had the good comprehension to the provocatus abortion and was eager to avoid it due to the religious behavior.